Hat die Befristung von Arbeitsverträgen einen Einfluss auf die berufliche Weiterbildung geringqualifiziert beschäftigter Personen? - Eva Reinowski; Jan Sauermann (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2008)
– Similar to other European countries, the use of fixed-term contracts in Germany has been deregulated since the 1980s. Though temporary employment can be seen as a possibility to re-enter the labour market, it is argued that temporary employment may lead to 'dead-ends' and to lower investments in further training. From a theoretical perspective, there are arguments for higher and for lower investments in further training for employers and employees. Thus, it is not clear whether firms and employees invest differently when temporary contracts are used. Using the German Mikrozensus 2004, this paper analyses the effect of temporary contracts an work-related training for low-skilled workers. To take systematic differences between temporary and permanent employees into account, we estimate a bivariate probit model for whether fixed-term employment affects participation in work-related training. We conclude that holding a temporary contract does not have systematic disadvantages in access to further training. The use of temporary contracts does not therefore worsen the situation of low-skilled employees in terms of their human capital accumulation.
Keywords: 330; befristeter Arbeitsvertrag - Auswirkungen; Weiterbildungsbeteiligung; betriebliche Weiterbildung; Niedrigqualifizierte